Policing through social media: a qualitative exploration - Fallik, Seth Wyatt (International journal of police science & management, 2020)
Social media, in the past decade, has been used to hold police accountable for their actions. There has been, however, a paucity of empirical research into how law enforcement uses social media. To explore this issue, this paper uses qualitative data emerging from ethnographic research conducted in a Southern American state. Participant observations of police officer deployments were paired with semi-structured interviews with officers from three law enforcement agencies. The extent and ways in which these officers used social media is explored. Findings indicate that social media is used to bring positive attention to law enforcement agencies and aid criminal investigations. Although the positive impact of social media was highlighted in these experiences, persistent problems and challenges also featured in the data. Finally, officer insights were drawn upon to make recommendations for future policing policy and research.